BIBLIOMETRIC MAPPING OF PAPERS ON GEOGRAPHICAL INFORMATION SYSTEMS (2007-2016) - Melo, Alexandre Vastella Ferreira de; Queiroz, Alfredo Pereira de (Boletim de Ciências Geodésicas, 2020)
The amount of researchers and scientific papers rapidly grows, annually. The metrics to analyze the quality and quantity of these publications have consolidated in the academic world. A bibliometric mapping of scientific papers on Geographic Information Systems (GIS) published between 2007 and 2016 was carried out. The sample analyzed 2,053 papers, extracted from twenty journals of the Web of Science Core Collection platform. The following were evaluated: total number of publications, production by area of knowledge and by country, authors, periodicals and the most cited words. The results shows that 2012 and 2013 were the most productive periods, and that the annual growth rate of publication was 1.8%. The most significant academic areas were Geography, Computer Science, Physical Geography, and Environmental Sciences/Ecology. The three major publishing clusters were North America, Western Europe, and Eastern Asia. The International Journal of Geographic Information Science was considered the most important journal. The most relevant topics were cellular automata, relationship between GIS and users, integration of GIS with remote sensing, different land use classification methods, and critical reflections on technologies and GIS.